The Future and challenge of Pragmatics in English Language Teaching - Mazulfah Mazulfah (Journal of Pragmatics Research, 2019)
This paper demonstrates about the future and challenge of pragmatics in English language teaching. In pragmatics, meaning in communication has an important role and it can be categorized into two elements such as verbal and nonverbal. It depends on various contexts, relationship between utterers, and social factors. In English language teaching, pragmatic is very important because the four language skills in language learning such as reading writing, listening and speaking do not occur in isolation in communicative texts or activities. So through forming a good pragmatic competence for the language learner, should be considered. As English has played an indispensable role in global communication, it is important for English language users, both native and non-native, to use clear, comprehensible and educated English that allows smooth communication and avoids misunderstandings in social interactions. Pragmatic competence can facilitate language users to successfully achieve their communicative aims in intercultural communication. Consequently, pragmatic elements have noticeable important in communication between speakers because such elements can hinder inaccuracies and misunderstandings during communication so teachers should teach pragmatic competence in language English classes through different activities and tasks.Keywords: Pragmatics, English language teaching, language competencies.